Corrosion behavior of high-pressure die-cast secondary AlSi9Cu3(Fe) alloy. (December 2022) - Monticelli, Cecilia; Zanotto, Federica; Balbo, Andrea; Grassi, Vincenzo; Fabrizi, Alberto; Timelli, Giulio
Abstract: This research investigated the corrosion behavior and susceptibility to stress corrosion cracking (SCC) of a high-pressure die-cast secondary AlSi9Cu3(Fe) alloy in 3.5 % NaCl solution. Microstructural observations by scanning electron microscope, coupled to energy dispersion spectroscopy, polarization curve recording, electrochemical impedance spectroscopy tests and slow strain rate tests evidenced the presence of critical surface segregation zones, where strong corrosion attack occurs due to composition differences and peculiar morphology of noble Al2 Cu phases. No SCC susceptibility was detected, but very strong localized corrosion attack and abundant hydrogen gas bubbling evolved from noble phase/α-Al matrix interphases, determining positive going potential transients. Highlights: Segregation and intermetallic precipitation in HPDC Al-Si-Cu secondary alloys. Al2 Cu phase and Si, Cu and Fe surface segregation affects corrosion behavior. Selective corrosion of α-Al phase in correspondence of die halves joining lines. Microgalvanic effects stimulated by nobler Al2 Cu phase and Fe-bearing compounds. No SCC susceptibility, but pitting corrosion at the noble phases /α-Al interfaces.